2013
DOI: 10.1002/iub.1152
|View full text |Cite
|
Sign up to set email alerts
|

IGF‐1 stimulated upregulation of cyclin D1 is mediated via STAT5 signaling pathway in neuronal cells

Abstract: Signal Transducer and Activator of Transcription (STATs) regulate various target genes such as cyclin D1, MYC, and BCL2 in nonneuronal cells which contribute towards progression as well as prevention of apoptosis and are involved in differentiation and cell survival. However, in neuronal cells, the role of STATs in the activation and regulation of these target genes and their signaling pathways are still not well established. In this study, a robust cyclin D1 expression was observed following IGF-1 stimulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 28 publications
4
14
0
Order By: Relevance
“…This is consistent with our previous work demonstrating that human tumor samples with high STAT5b expression were associated with shorter survival wherein, we have shown that STAT5b can be activated by ΔEGFR and then associate together in the nucleus to affect gene transcription by directly binding to regulatory DNA regions . Our findings in this article support this conclusion, as we demonstrated high expression of the known downstream targets of STAT5b cyclin D1, aurora kinase A and Bcl‐xL . Although this would predict that STAT5b overexpression would drive tumor cell proliferation, we were unable to show a statistical increase in mitotic activity in tumors induced by STAT5b + PDGFB relative to those induced by PDGFB alone.…”
Section: Discussionsupporting
confidence: 92%
“…This is consistent with our previous work demonstrating that human tumor samples with high STAT5b expression were associated with shorter survival wherein, we have shown that STAT5b can be activated by ΔEGFR and then associate together in the nucleus to affect gene transcription by directly binding to regulatory DNA regions . Our findings in this article support this conclusion, as we demonstrated high expression of the known downstream targets of STAT5b cyclin D1, aurora kinase A and Bcl‐xL . Although this would predict that STAT5b overexpression would drive tumor cell proliferation, we were unable to show a statistical increase in mitotic activity in tumors induced by STAT5b + PDGFB relative to those induced by PDGFB alone.…”
Section: Discussionsupporting
confidence: 92%
“…While Bcl6 appears to repress multiple serial components of individual pathways, it could also act through common effectors of parallel signals. In line with this hypothesis, Cyclin d1/d2 genes were found to be down-regulated by Bcl6 overexpression in vitro ( Figure 1D, Supplementary Table S1), and are known to be up-regulated by pathways driving progenitor self-renewal, including Wnt (Shtutman et al, 1999) but also SHH (Kasper et al, 2006;Katoh and Katoh, 2009), FGF/IGF (Kalita et al, 2013;Nilsson et al, 2012), and Notch (Cohen et al, 2010). Moreover, Cyclin d1/d2 are key promoters of cortical progenitor proliferation and consequently block neurogenesis (Lange et al, 2009;Pilaz et al, 2009;Tsunekawa et al, 2012).…”
Section: Bcl6 Promotes Neurogenesis Through Cyclin D Inhibitionmentioning
confidence: 56%
“…For instance, the deletion of Gsk3a/b, a major intracellular component of the β-catenin destruction complex, increases the proliferation of radial glial cells at the expense of their differentiation by altering not only Wnt but also Notch and FGF signaling activity (Kim et al, 2009). Also, some key effectors genes such as Cyclin d1/d2 are found as common targets of most morphogen pathways depending on cellular context (Cohen et al, 2010;Kalita et al, 2013;Katoh and Katoh, 2009;Nilsson et al, 2012;Shtutman et al, 1999). How these intermingled pathways are effectively shut down during neurogenesis is therefore an important and complex issue that remains largely unresolved.…”
Section: Introductionmentioning
confidence: 99%
“…However, stable knockdown of PKM2 using a PKM2-specific small hairpin RNA (shRNA) vector (Supplementary Figure S1) abolished the IGF-1-induced growth in these cells (Figure 1A). In parallel, the IGF-1-induced expression of CCND1, a marker of IGF-1 signaling activation [29], was also disrupted in the PKM2 knockdown cells (Figure 1B). …”
Section: Resultsmentioning
confidence: 99%
“…The STAT5-induced increase of CCND1 expression is one of the crucial effector responses in IGF-1-induced cell proliferation [29]. We investigated whether PKM2 can increase CCND1 expression under IGF stimulation and subsequent cell growth via tethering the STAT5 activity.…”
Section: Resultsmentioning
confidence: 99%